Language to Light On:: Dionne Brand and the Rebellious Word - Fraser, Kaya (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2005)
In No Language is Neutral and Land to Light On, Dionne Brand suggests that language can be used as a willful act of resistance against a hegemonic, seemingly monolithic "standard English." In the tradition of what Deleuze and Guattari call "minor literature," Brand's literature effects a subtle, yet crucial, internal alteration of the dominant language by means of deterritorialization. The result is a new, at once subversive and creative way of inhabiting language. In No Language is Neutral, lived experience and the words to convey it are integrated; the book celebrates empowerment and agency rooted in language. However, Brand's tone shifts from determined to ambivalent in Land to Light On. The speaker feels disempowered and harmed by language, recognizing not only its inadequacy and probable failure to effect lasting political change but also its power to gloss over subversive truth-telling, to which even the poet is susceptible.